2020
DOI: 10.1080/11101849.2020.1789403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between complete blood picture indices and presepsin as early prognostic markers in septic shock patients

Abstract: Comparative study between complete blood picture indices and presepsin as early prognostic markers in septic shock patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(58 reference statements)
0
1
0
1
Order By: Relevance
“…Mandal et al analyzed NLR value in predicting mortality and reported a very high AUC of 0.800 with NLR > 10 as optimal cut-off [ 21 ]. A more recent study from 2020 by El Said et al evaluated both NLR and presepsin and found significant prognostic values: AUC = 0.890 with 92% sensitivity and 83% specificity at a 2100 ng/mL cut-off for presepsin and AUC = 0.758 with 75% sensitivity and 79% specificity for NLR = 17 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mandal et al analyzed NLR value in predicting mortality and reported a very high AUC of 0.800 with NLR > 10 as optimal cut-off [ 21 ]. A more recent study from 2020 by El Said et al evaluated both NLR and presepsin and found significant prognostic values: AUC = 0.890 with 92% sensitivity and 83% specificity at a 2100 ng/mL cut-off for presepsin and AUC = 0.758 with 75% sensitivity and 79% specificity for NLR = 17 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Na mesma linha, vários autores (el Said et al, 2020), (Zhu et al, 2019),(S. Lee et al, 2022), descobriram que os níveis de presepsina nos sobreviventes são inferiores aos dos não sobreviventes, sendo que os sobreviventes foram encontrados valores de 1828 pg/ml, 556-957,5 pg/ml, < 821 respectivamente, enquanto nós não sobreviventes os valores encontrados foram 3303 pg/ml, 1622-2000 pg/ml, ≥821 pg/ml; da mesma forma, outros autores (Wen et al, 2019), (Khashaba et al, 2022), encontraram achados semelhantes, assim, embora as populações estudadas fossem diferentes, o resultado foi semelhante, ou seja, os níveis de presepsina foram mais altos naqueles pacientes que não sobreviveram, enquanto naqueles que sobreviveram os valores de presepsina foram mais baixos; portanto, a presepsina mostra grande valor em fornecer um prognóstico de mortalidade.…”
Section: Biomarcador Cd14 Solúvelunclassified